2019
DOI: 10.5897/ajar2019.13969
|View full text |Cite
|
Sign up to set email alerts
|

Performance of CIP and Dutch potato varieties under Rwanda climate conditions

Abstract: In attempt to develop new potato varieties with the current market lead traits, nine Dutch potato varieties namely Fabula, Panamela, Sagitta, Challenger, Sifra, Rosi, Memphis, Taurus and Derby, and International Potato Center (CIP) varieties Kinigi and Kirundo were evaluated in three Rwandan sites for two growing seasons in a randomized complete block design (RCBD) with tree replications. The data collected consists of plant vigor, late blight incidence and severity, yields and processing qualities. The collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Also in Rwanda, the Dutch variety Taurus responds better to the industry's needs compared to the CIP varieties Kinigi and NAROPOT 4/Rwangume. Previous studies reported as well that Taurus is among the best varieties to produce crisps (Rukundo et al 2019). In Uganda, however, both CIP and Dutch varieties are popular among the processing industry, and they respond well to its needs.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Also in Rwanda, the Dutch variety Taurus responds better to the industry's needs compared to the CIP varieties Kinigi and NAROPOT 4/Rwangume. Previous studies reported as well that Taurus is among the best varieties to produce crisps (Rukundo et al 2019). In Uganda, however, both CIP and Dutch varieties are popular among the processing industry, and they respond well to its needs.…”
Section: Discussionmentioning
confidence: 89%
“…Maingi et al (2015),Kaguongo et al (2014) andRukundo et al (2019) who reported that Dutch Robijn is a low yielding variety susceptible to pests and diseases and that the cultivation of Dutch varieties requires additional inputs including agro-chemicals to achieve higher yields leading to negative implications on the cost of production and lower crop sustainability. The breeders, however, believe that CIP varieties like Gikungu, KACHPOT 1, Kinigi, NAROPOT 4/Rwangume and Shangi meet farmers' needs well due to their tolerance to diseases, high yield, skin/ esh color and high fresh market demand.…”
mentioning
confidence: 99%
“…The field trials were conducted in two growing seasons: season B of 2018 starting in February and ending in June and season A of 2019 ranging between August and December. In each growing season, trials were conducted in four sites representing the major potato agriculture regions in Rwanda, namely, Congo Nile watershed divine, Highland of Buberuka, and Highland of Virunga (NISR, 2019; Rukundo, 2019). Trials were established at Nyamagabe and Gakuta RAB research stations located in Congo Nile watershed divine zone, Rwerere RAB research station representing the Buberuka Highland agroecological zone, and Kinigi RAB research station representing the Virunga agroecological zone.…”
Section: Methodsmentioning
confidence: 99%
“…Most of current popular potato varieties grown in Rwanda were developed before 1994 genocide that destroyed most of the country research capacity including human resources and infrastructures (Rukundo 2019). These varieties were developed based on the needs of that time; nowadays, the needs have changed.…”
Section: Cabi Agriculture and Biosciencementioning
confidence: 99%